2020
DOI: 10.1136/annrheumdis-2020-217658
|View full text |Cite
|
Sign up to set email alerts
|

SLE patients are not immune to covid-19: importance of sending the right message across

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 3 publications
1
17
0
1
Order By: Relevance
“…In our opinion, rheumatic disease patients are not immune to SARS-CoV-2 infection, which is coincide with Sawalha AH and Goyal M et al's views [7,8]. This opinion has been reinforced by the data from The COVID-19 Global Rheumatology Alliance Global Registry [9], which showed that 600 patients with rheumatic disease who have been diagnosed with COVID-19, including 144 RA patients and 72 SLE patients.…”
Section: Evidences For Sars-cov-2 Susceptibility In Patients With Rhesupporting
confidence: 74%
“…In our opinion, rheumatic disease patients are not immune to SARS-CoV-2 infection, which is coincide with Sawalha AH and Goyal M et al's views [7,8]. This opinion has been reinforced by the data from The COVID-19 Global Rheumatology Alliance Global Registry [9], which showed that 600 patients with rheumatic disease who have been diagnosed with COVID-19, including 144 RA patients and 72 SLE patients.…”
Section: Evidences For Sars-cov-2 Susceptibility In Patients With Rhesupporting
confidence: 74%
“…As Nikipharou et al [20] already pointed out, social media platforms provide novel ways for opinion sharing, learning and development, which is especially important in times of uncertainties during a pandemic. Notably, social media can effectively increase the impact of scientific [23][24][25][26][27] publications which might be of interest to researchers and scientific journals alike [21]. Social media can direct attention and increase participation for digital crowdsourcing projects, such as the COVID-19 Global Rheumatology Alliance registries or healthcare policy projects.…”
Section: Discussionmentioning
confidence: 99%
“…In the first period of the COVID-19 pandemic, treatment with hydroxychloroquine (HCQ) was suggested as an inhibitor of SARS-CoV-2 in vitro, but recent studies involving SLE patients have demonstrated that the doses used in treatment of SLE are not protective against severe COVID-19 infection [5][6][7][8][9][10]. On the other hand glucocorticoids might increase the risk of hospitalisation and a subsequent severe outcome [11,12].…”
Section: Introductionmentioning
confidence: 99%